2017
DOI: 10.1093/mnras/stx1015
|View full text |Cite
|
Sign up to set email alerts
|

Black hole binaries dynamically formed in globular clusters

Abstract: We investigate properties of black hole (BH) binaries formed in globular clusters via dynamical processes, using direct N-body simulations. We pay attention to effects of BH mass function on the total mass and mass ratio distributions of BH binaries ejected from clusters. Firstly, we consider BH populations with two different masses in order to learn basic differences from models with single-mass BHs only. Secondly, we consider continuous BH mass functions adapted from recent studies on massive star evolution … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
107
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(116 citation statements)
references
References 53 publications
7
107
1
Order By: Relevance
“…The progenitors of these BBHs are still unknown and under intensively investigation (see e.g. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]). These LIGO/Virgo BBHs present a much heavier mass distribution (in particular the sourceframe primary mass of GW170729 event can be as heavy as 50.2 +16.2 −10.2 M [7]) than that inferred from X-ray observations [28][29][30][31], which would challenge the formation and evolution mechanisms of astrophysical black holes.…”
Section: Introductionmentioning
confidence: 99%
“…The progenitors of these BBHs are still unknown and under intensively investigation (see e.g. [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]). These LIGO/Virgo BBHs present a much heavier mass distribution (in particular the sourceframe primary mass of GW170729 event can be as heavy as 50.2 +16.2 −10.2 M [7]) than that inferred from X-ray observations [28][29][30][31], which would challenge the formation and evolution mechanisms of astrophysical black holes.…”
Section: Introductionmentioning
confidence: 99%
“…The core of globular clusters (10 5 -10 6 M ⊙ ) has long been investigated as a formation site of BBHs in many previous works (e.g. Portegies Zwart & McMillan 2000;O'Leary et al 2006;Sadowski et al 2008;Downing et al 2010Downing et al , 2011Banerjee et al 2010;Tanikawa 2013;Bae et al 2014;Rodriguez et al 2015Rodriguez et al , 2016Fujii et al 2017;Park et al 2017;Askar et al 2017;Hong et al 2018;Zevin et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…4, where the absolute value of the relative error between the hybrid and NR amplitude and phase are shown. The quantity ∆X is defined as 22 . The errors in the amplitude are larger than the ones in the phase, but they are below the 1% threshold.…”
Section: B Hybridization Examplementioning
confidence: 99%
“…Recently, population synthesis studies [21][22][23][24] have shown that active galactic nuclei and globular clusters can host a population of moderate and highly eccentric binaries emitting in the frequency band of ground-based detectors. Therefore, the increase in sensitivity of the detectors will increase the likelihood to detect binary systems with non-negligible eccentricities.…”
Section: Introductionmentioning
confidence: 99%